When Victims are Criminalized: Reflections on the Politics of Criminal Law from the Baiq Nuril Case - Wakhidatul Mubarokah; Ali Masyhar Mursyid; Cahya Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
The Baiq Nuril case is a clear reflection of the political problems of criminal law in Indonesia, especially in the context of protecting victims of sexual violence and the application of the Electronic Information and Transaction Law (ITE Law). Baiq Nuril, a victim of verbal harassment by her superior, was criminalized through Article 27 paragraph (1) of the ITE Law after she recorded an obscene conversation as a form of self-protection. This research uses a normative juridical approach by analyzing relevant legal instruments and their application in the Baiq Nuril case. The results show that the use of the article contains structural bias and shows an imbalance of perspectives in the criminal justice system, which tends to ignore the position of victims as well as the social context and power relations that surround them. In addition, the article's multiple interpretations open space for criminalization of victims, especially women, instead of providing protection. This case emphasizes the importance of criminal law reform oriented towards substantive justice and in favor of victims, as well as the need to revise the ITE Law so that it does not become a tool of repression against vulnerable groups. The amnesty granted by the President to Baiq Nuril is a political corrective step, but has not touched the root of systemic problems in law enforcement that have not been in favor of victims of gender-based violence.